A Mouse Model of Damp-Heat Syndrome in Traditional Chinese Medicine and Its Impact on Pancreatic Tumor Growth - Jiao, Juying; Cheng, Chien-shan; Xu, Panling; Yang, Peiwen; Ruan, Linjie; Chen, Zhen (Frontiers in Oncology, 2022)
Background: Damp-heat syndrome is one of the most important syndrome types in the traditional Chinese medicine (TCM) syndrome differentiation and treatment system, as well as the core pathogenesis of pancreatic cancer (PC) which remains a challenge to medical researchers due to its insidious onset and poor prognosis. Great attention has been given to the impact of damp-heat syndrome on tumorigenesis and progression, but less attention has been given to damp-heat modeling per se. Studying PC in a proper damp-heat syndrome animal model can recapitulate the actual pathological process and contribute to treatment strategy improvement. Methods: Here, an optimized damp-heat syndrome mouse model was established based on our prior experience. The Fibonacci method was applied to determine the maximum tolerated dosage of alcohol for mice. Damp-heat syndrome modeling with the old and new methods was performed in parallel of comparative study about general appearance, food intake, water consumption and survival. Major organs, including the liver, kidneys, lungs, pancreas, spleen, intestines and testes, were collected for histological evaluation. Complete blood counts and biochemical tests were conducted to characterize changes in blood circulation. PC cells were subcutaneously inoculated into mice with damp-heat syndrome to explore the impact of damp-heat syndrome on PC growth. Hematoxylin-eosin staining, Masson staining and immunohistochemistry were performed for pathological evaluation. A chemokine microarray was applied to screen the cytokines mediating the proliferation-promoting effects of damp-heat syndrome, and quantitative polymerase chain reaction and Western blotting were conducted for results validation. Results: The new modeling method had the advantages of mouse-friendly features, easily accessible materials, simple operation, and good stability. More importantly, a set of systematic indicators was proposed for model evaluation. The new modeling method verified the pancreatic tumor-promoting role of damp-heat syndrome. Damp-heat syndrome induced the proliferation of cancer-associated fibroblasts and promoted desmoplasia. In addition, circulating and tumor-located chemokine levels were altered by damp-heat syndrome, characterized by tumor promotion and immune suppression. Conclusions: This study established a stable and reproducible murine model of damp-heat syndrome in TCM with systematic evaluation methods. Cancer associated fibroblast-mediated desmoplasia and chemokine production contribute to the tumor-promoting effect of damp-heat syndrome on PC.